Molecular pathogenesis of chronic lymphocytic leukemia - Gaidano, Gianluca; Foà, Robin; Dalla-Favera, Riccardo (The Journal of clinical investigation, 2012)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults. Here, we highlight important genetic alterations that contribute to tumorigenesis, clinical progression, and chemorefractoriness of CLL. All CLLs share a common gene expression profile that suggests derivation from antigen-experienced B cells, a model supported by frequent B cell receptor repertoire skewing and stereotypy. Many CLL patients carry mutated immuno-globulin heavy-chain variable genes, while approximately 35% harbor unmutated IgV genes, which are associated with an inferior outcome. Deletion of chromosome 13q14, which is the most common genetic mutation at diagnosis, is considered an initiating lesion that frequently results in disruption of the tumor suppressor locus DLEU2/MIR15A/MIR16A. Next-generation sequencing has revealed additional recurrent genetic lesions that are implicated in CLL pathogenesis. These advancements in the molecular genetics of CLL have important implications for stratifying treatment based on molecular prognosticators and for targeted therapy.